Mean platelet volume is more important than age for defining reference intervals of platelet counts - Ittermann, Till; Feig, Martin A.; Petersmann, Astrid; Radke, Dörte; Greinacher, Andreas; Völzke, Henry; Thiele, Thomas (PloS one, 2019)
Platelet count is known to be associated with sex, age and mean platelet volume (MPV). Sex and age were proposed for adjustment of platelet count reference intervals, but MPV is currently not used for further adjustment. We investigated the association of MPV, age and sex with platelet counts and established individualized reference ranges respecting MPV. The association of platelet count with age, sex and MPV was assessed in healthy participants (n = 3,033 individuals; 1,542 women) in the cross-sectional population-based cohort Study of Health in Pomerania. Reference intervals respecting age, sex, and MPV were estimated using quantile regressions for the 2.5th and 97.5th percentile. Women had higher platelet counts than men (239 vs. 207 x109/L, p<0.001). Platelet counts correlated with age (p<0.001) and MPV (p<0.001). Quantile regression of lower and upper platelet count limits correlated less with age in female (p = 0.047 for 2.5th percentile; p = 0.906 for 97.5th percentile) and male subjects (p = 0.029 for 2.5th percentile; p = 0.195 for 97.5th percentile) compared to MPV (p<0.001 for upper and lower limit for both sexes). After adjustment for MPV, age did no longer correlate with the 2.5th (p = 0.165) or 97.5th percentile (p = 0.999) of platelet count. In contrast, after adjustment for age, MPV levels still significantly correlated with 2.5th, 50th and 97.5th percentile (p<0.001). MPV and sex have a stronger association with platelet count than age. MPV should be considered to adjust platelet count reference intervals and needs to be respected as confounder for platelet counts in epidemiological studies and clinical practice.